Innovative development of community business models in commercial complexes under the background of the new era - Yan, Kailun (International Theory and Practice in Humanities and Social Sciences, 2025)
In todays rapidly changing new era, the community business model of commercial complex is undergoing profound changes and innovations. This study is committed to exploring the root, path and future trend of this change. By comprehensively integrating various research methods and deeply analyzing data cases, it reveals the multiple driving factors of business model innovation in commercial complex communities. Consumption upgrades, the widespread application of digital technology, the evolution of urban lifestyles, and the impact of the epidemic have jointly contributed to this wave of innovation. In terms of online and offline integration and intelligent services, the research reveals the diversity and advantages of innovation paths. At the same time, facing the differentiation of residents needs, the pressure of cost and the security of technology application, this study also gives targeted solutions. This not only provides a solid theoretical basis for the development of commercial complexes in the field of community commerce, but also points out the practical direction for its sustainable development, helping commercial complexes achieve more steady and diversified growth in the new era.